Development of Creative House Educational Game Tools to Develop Cognitive Aspects in Children Aged 5-6 Years - Rodhiah Umri; Leli Fertiliana Dea; Yuning Eka Rahmawati (CV. Creative Tugu Pena, 2025)
This study aims to develop and test the effectiveness of Creative House Educational Play Tools (APE) in improving the cognitive abilities of children aged 5–6 years. The method used is Research and Development (R&D) with the Borg and Gall model which is simplified into seven stages, including potential and problem analysis, data collection, product design, expert validation, revision, limited trial, and final revision. The subjects of the study were 12 children aged 5–6 years at RA Miftahut Tholibin Sukadana Jaya with saturated sampling techniques, and involved teachers, school principals, media experts, and material experts as validators. The results of the study showed that APE Rumah Kreatif is feasible and effective in improving children's cognitive abilities, shown by a significant increase from the category of Not Yet Developed to Start Developing, Developing as Expected, to Developing Very Well after the use of media. In addition, children become more active, enthusiastic, and able to understand symbolic concepts better through play activities. Thus, APE Rumah Kreatif is proven to be an innovative learning medium that is able to create active, interactive, and fun learning and contribute to the development of early childhood cognitive abilities based on play-based learning.